MENGUKIR BUDAYA GLOBAL DI SEKOLAH LOKAL: INOVASI KEPEMIMPINAN DI SDN 11 KAMPUNG BATU DALAM KECAMATAN DANAU KEMBAR KABUPATEN SOLOK - Weni Yulastri; Yusparni Yetti; Husni Nofrita; Rinda Riska; Ratnawilis; Fitri Sari Angkat; Syovia Lolita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research reveals the challenges and solutions in implementing culturally-based global educational leadership at SDN 11 Kampung Batu Dalam, Solok. Several issues were identified, such as weak discipline culture, low professional awareness of teachers, minimal adaptation of global values, and structural barriers within the school organization. Referring to transformational and multicultural leadership theories, as well as findings from national/international journals, this article formulates strategies to strengthen inclusive vision, integrate multicultural curricula, utilize local wisdom, foster community partnerships, provide continuous training, and implement distributed leadership models. It is also equipped with concrete innovations such as 'Cultural Exemplary Teachers', 'Cultural Fridays', and global online collaborations. It is hoped that these strategies can shape an inclusive, culturally responsive, and globally competitive school.